-0.5(y-12)=-0.1(y+1)

Simple and best practice solution for -0.5(y-12)=-0.1(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.5(y-12)=-0.1(y+1) equation:


Simplifying
-0.5(y + -12) = -0.1(y + 1)

Reorder the terms:
-0.5(-12 + y) = -0.1(y + 1)
(-12 * -0.5 + y * -0.5) = -0.1(y + 1)
(6 + -0.5y) = -0.1(y + 1)

Reorder the terms:
6 + -0.5y = -0.1(1 + y)
6 + -0.5y = (1 * -0.1 + y * -0.1)
6 + -0.5y = (-0.1 + -0.1y)

Solving
6 + -0.5y = -0.1 + -0.1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '0.1y' to each side of the equation.
6 + -0.5y + 0.1y = -0.1 + -0.1y + 0.1y

Combine like terms: -0.5y + 0.1y = -0.4y
6 + -0.4y = -0.1 + -0.1y + 0.1y

Combine like terms: -0.1y + 0.1y = 0.0
6 + -0.4y = -0.1 + 0.0
6 + -0.4y = -0.1

Add '-6' to each side of the equation.
6 + -6 + -0.4y = -0.1 + -6

Combine like terms: 6 + -6 = 0
0 + -0.4y = -0.1 + -6
-0.4y = -0.1 + -6

Combine like terms: -0.1 + -6 = -6.1
-0.4y = -6.1

Divide each side by '-0.4'.
y = 15.25

Simplifying
y = 15.25

See similar equations:

| 0=2x^2-5x+3 | | 3x^-4/27x^2 | | 1/2x+5/3=-3/2x-7/3 | | 2(x-5)=x+5x | | (x^2-4x+4)/(x^2+4x-12)*(2x+12)/(6x^2-13x+2) | | s^2+6s+5=0 | | (2/x)+4=(2/3x) | | 8m-29=-22+7m | | 13.7b-6.5=23b+8.3 | | 5n-25=-13+3n | | -7.64+10000= | | y=-3*1+2 | | y=-3*-2 | | 0.6(y+1.5)=-2.1(y-3) | | 6(3+3x)-2=106 | | -2/5(n-1/8)=1/2(n-1/6) | | 10-2m=3m+25 | | 1729x-258=433x-474 | | (2/x^2+12x+36)+(5/x^2+x-30) | | X^2+10x+9=(x+1)(ax+b) | | -2(x-3)+4(2-x)= | | -5y-8=-7y-16 | | 19x-11-17x+14=2x+3 | | [5x-7]=33 | | 8-[(-3+7)-(3-9)]= | | 5+4x-7=4x-2 | | -10-(-3)= | | 0-8y=5 | | -4.07+2.3= | | T=C(2+AB) | | 5(2y+2)-(y+3)= | | abs(3x-4)= |

Equations solver categories